Developments of furan and benzodifuran semiconductors for organic photovoltaics. Issue 12 (28th March 2015) - Huang, Peishen; Du, Jia; Biewer, Michael C.; Stefan, Mihaela C.
<x xml:space="preserve">Abstract</x> This review describes the developments of organic photovoltaic materials containing furan or benzo[1, 2-b:4, 5-b′]difuran (BDF) building blocks.